Multiple Positive Solutions of a Nonlinear Four-Point Singular Boundary Value Problem with a p-Laplacian Operator on Time Scales. (5th March 2009) - Hong, Shihuang
Abstract : We present sufficient conditions for the existence of at least twin or triple positive solutions of a nonlinear four-point singular boundary value problem with ap -Laplacian dynamic equation on a time scale. Our results are obtained via some new multiple fixed point theorems.